Why and How the Liberalisation of the Cannabis Market in Germany Should Occur - Justus Haucap; Leon Knoke (Wirtschaftsdienst)
Abstract This article summarises the arguments in favour of legalising cannabis and makes proposals for the design of the regulatory framework. The main argument for a regulated cannabis market is not the expected tax revenues or the legal jobs that would be created, but the improved youth and health protection in a state-regulated cannabis market. While consumption of legal addictive substances such as tobacco and alcohol has been successfully curbed, cannabis consumption has been increasing for years despite prohibition. A well designed market order with appropriate market regulation and taxation is crucial for effective youth and health protection.